Chosen problems in forensic examining of signatures placed on paintings - Leśniak, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In the context of current forensic knowledge and practice, using the handwriting analysis method to examine a painter’s signature does not give rise to any objections. It allows such an examination to be more transparent. The article presents a certain specificity which characterizes painter signatures. Such distinctions reveal themselves at various stages of analysis: examining the location of the questioned signature; qualifying examination of the questioned signature; determining the scope of handwriting features considered under the examination; determining the range of variability in handwriting characteristics in the comparative material; determining the degree of variability in the same characteristics in the questioned signature. The article also raises the issue of experts’ competencies, particularly significant in examining painting signatures.In the context of current forensic knowledge and practice, using the handwriting analysis method to examine a painter’s signature does not give rise to any objections. It allows such an examination to be more transparent. The article presents a certain specificity which characterizes painter signatures. Such distinctions reveal themselves at various stages of analysis: examining the location of the questioned signature; qualifying examination of the questioned signature; determining the scope of handwriting features considered under the examination; determining the range of variability in handwriting characteristics in the comparative material; determining the degree of variability in the same characteristics in the questioned signature. The article also raises the issue of experts’ competencies, particularly significant in examining painting signatures.
Keywords: metody analizy pisma ręcznego; analiza sygnatur na obrazach; kompetencje ekspertów